The Implementation of Character Education in Teaching English at SMP Muhammadiyah 4 Pekanbaru - Annisya Ulkhairi (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
This research was aimed to describ about the implementation of character education in teaching English in online learning. Since there is transition between tradisional learning to online learning, this topic will be interesting to be researched. This was conducted at SMP Muhammadiyah 4 Pekanbaru.This research can be categorized as phenomenological research which employs the qualitative approach. The instruments used were observation sheets and interview guides. The data were collected through observation, interview, and documents. The subjects of the research were the English teacher of SMP Muhammadiyah 4 Pekanbaru.The result of this study shows that the implementation of character education in teaching English in online learning of SMP Muhammadiyah 4 Pekanbaru. It was integrated into the planning stage, the teaching and learning stage, and the evaluation stage by developing essential virtues, including being religious, discipline, honesty, independence, responsibility, hardwork/persistence, curiosity, creativity, honesty, friendliness/ communicative, appreciation of acheivement. There are some supporting and inhibiting factors faced in implementing character education including (1) teacher (2) students (3) parents who support to implement the values in teaching and learning process and also some challenges such as (1). Lack of training (2) no direct interaction (3) lack of students’ motivation and manner (4) lack of parents’ support and ( technical error). In addition there are some ways that teacher do to solve the problems in this research such (1) Learn again and again. (2) approach the students (3) collaborate with parents.Keywords: implementation, character education, online learning.